2020
DOI: 10.1007/s10555-020-09885-8
|View full text |Cite
|
Sign up to set email alerts
|

CDK7 inhibitors as anticancer drugs

Abstract: Cyclin-dependent kinase 7 (CDK7), along with cyclin H and MAT1, forms the CDK-activating complex (CAK), which directs progression through the cell cycle via T-loop phosphorylation of cell cycle CDKs. CAK is also a component of the general transcription factor, TFIIH. CDK7-mediated phosphorylation of RNA polymerase II (Pol II) at active gene promoters permits transcription. Cell cycle dysregulation is an established hallmark of cancer, and aberrant control of transcriptional processes, through diverse mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
115
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(134 citation statements)
references
References 140 publications
0
115
0
Order By: Relevance
“…Its expression frequently increases in many cancers and is important for tumor development ( 10 , 12 ). A number of CDK7 inhibitors are considered to be potential drug candidates for cancer therapy because they are highly cytotoxic to tumor cells only ( 13 , 21 , 22 ). One main concern regarding the application of CDK7 inhibitors in cancer therapy is the variable sensitivity of different cancer types to CDK7 inhibition, which has been found in preclinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Its expression frequently increases in many cancers and is important for tumor development ( 10 , 12 ). A number of CDK7 inhibitors are considered to be potential drug candidates for cancer therapy because they are highly cytotoxic to tumor cells only ( 13 , 21 , 22 ). One main concern regarding the application of CDK7 inhibitors in cancer therapy is the variable sensitivity of different cancer types to CDK7 inhibition, which has been found in preclinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Rasool et al demonstrated that THZ1 attenuated the AR-signaling and maintained efficacy in CRPC and enzalutamide-resistant PCa cells 47 . Also, CDK7 selective inhibitors have been developed, such as SY1365 and CT7001, and evaluated in clinical trials in other advanced solid tumors 100,101 . ERG overexpression is observed in a large group of primary PCa and CRPC.…”
Section: Promising Pharmacological Targetsmentioning
confidence: 99%
“…Furthermore, it has recently been reported that four CDK7 inhibitors (ICEC0942, SY-1365, SY-5609, and LY3405105), which were developed to improve the poor bioavailability and insufficient permeability of BS-181, have progressed to phase I/II clinical trials for evaluating their antitumor efficacy [ 43 ]. Although only ICEC0942 among these four CDK inhibitors is a BS-181 analog that has been developed to retain the CDK7 selectivity of BS-181 [ 44 ], and is thus highly likely to induce extrinsic apoptosis through TRAIL/DR5 upregulation in tumor cells, the contributions of these CDK7 inhibitors to the extrinsic TRAIL/DR5-dependent apoptosis induction in tumor cells and their synergistic cytotoxic effect exerted by cotreatment with rTRAIL remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%